2020
DOI: 10.1016/j.chembiol.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry and Biology of Ferroptosis

Abstract: Àinhibitor (Gout et al., 2001). However, sulfasalazine has very low potency, and is metabolically unstable in vivo, making it difficult to use in animal studies; it is best used as a confirmatory tool in cell culture studies. The compounds DPI2 (Yang et al., 2014) and RSL5 (Yang and Stockwell, 2008) have similar effects as erastin, and may also be system x c À inhibitors, although this potential mechanism has not been tested directly (Figure 1; Table 1).The amino acid and neurotransmitter glutamate has also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
214
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(219 citation statements)
references
References 104 publications
3
214
0
2
Order By: Relevance
“…Ferroptosis is recently discovered iron-dependent cell death fueled by lipid peroxidation, which differs from necrosis and apoptosis [ 322 324 ]. Mitochondrial metabolism involved series of substrates consumption, is primary source of ROS via Fenton reaction that ferrous iron mixed with hydrogen peroxide (H 2 O 2 ) is equipped with strong oxidizability to oxidize many known intracellular compounds such as carboxylic acids, alcohols and esters into inorganic states with significant oxidation effect [ 325 ].…”
Section: Hypoxia and Targeted Therapy Via Epigenetic Interferencementioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis is recently discovered iron-dependent cell death fueled by lipid peroxidation, which differs from necrosis and apoptosis [ 322 324 ]. Mitochondrial metabolism involved series of substrates consumption, is primary source of ROS via Fenton reaction that ferrous iron mixed with hydrogen peroxide (H 2 O 2 ) is equipped with strong oxidizability to oxidize many known intracellular compounds such as carboxylic acids, alcohols and esters into inorganic states with significant oxidation effect [ 325 ].…”
Section: Hypoxia and Targeted Therapy Via Epigenetic Interferencementioning
confidence: 99%
“…Interestingly, it’s reported that hypoxic tumors with HIF-1 over-expression inhibits acyl-CoA dehydrogenases leads to tumor progression via ROS alteration [ 209 ]. Over the past 20 years, small-molecule inhibitors, including system x c -Inhibitors, GPX4 inhibitors, RTAs, CoQ10 pathway inhibitors, endoperoxides, and iron chelators and sources inhibitors etc., have been applied in ferroptosis-associated diseases [ 322 ], and mechanisms behind these inhibition effects may reappear in HIF signaling, which remains under-reported.…”
Section: Hypoxia and Targeted Therapy Via Epigenetic Interferencementioning
confidence: 99%
“…To determine whether H 2 O 2 -mediated cell death occurs via apoptosis or ferroptosis, the cells were treated with Liperfluo or Annexin V and PI followed by flow cytometry analysis. Liperfluo is a ferroptosis marker [ 31 ] and Annexin V is an apoptosis marker. Our results showed that Liperfluo increased more than Annexin V in both HeLa and SAS ρ 0 cells after 3-h H 2 O 2 treatment (1.55 vs. 1.15-fold in HeLa ρ 0 cells and 3.79 vs 1.63-fold in SAS ρ 0 cells, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During lipid oxidation, GPX4 is the primary enzyme that prevents ferroptosis (Stockwell et al, 2017;Seibt et al, 2019). Many studies have shown that ROS inhibitors (e.g., ferrostatins-1, liproxstatin-1, vitamin E, vitamin C, and beta-carotene), along with GPX4 and its promoters (e.g., dopamine and selenium), are effective in preventing ferroptosis in animal models (Imai et al, 2017;Stockwell, 2018;Bai et al, 2019;Tang and Tang, 2019;Stockwell and Jiang, 2020). For example, the ROS inhibitors ferrostatin-1 and vitamin C aggravate ROS generation and block lipid peroxidation, and vitamin E may inhibit lipoxygenases (Zilka et al, 2017;Hinman et al, 2018;.…”
Section: Inhibitors Of Lipid Ros Generationmentioning
confidence: 99%